Pendidikan Akhlak Responsif Gender Perspektif Mahmud Syaltut dan Implikasinya terhadap Pendidikan Anak - Rahmadani Akbar; Zamalkani Ahamada (Universitas Muhammadiyah Gresik, 2026)
This study examines the concept of gender-responsive moral education from Mahmud Syaltut's perspective and its implications for children's education. Mahmud Syaltut's thoughts on gender justice, which emphasize the equality of men and women in creation, human dignity, and spiritual and social responsibilities, offer a strong philosophical foundation for formulating gender-responsive moral education. This research is a qualitative study with a literature study type and an Islamic educational philosophy approach. The primary data sources are Mahmud Syaltut's works, namely Al-Islām: ‘Aqīdah wa Sharī‘ah and Min Taujihati al-Islām, while secondary data sources are books, journal articles, and relevant dissertations. The data analysis technique used content analysis combined with conceptual and hermeneutic analysis, including data reduction, text interpretation, philosophical analysis (ontological, epistemological, and axiological), and pedagogical analysis. The results of the study indicate that Syaltut's thoughts have important implications for children's moral education, including: (1) instilling awareness of gender equality from an early age, (2) the role of parents and teachers as role models in the equal division of domestic tasks, the use of gender-neutral language, and providing equal opportunities, (3) methods of instilling gender justice values ​​through dialogue and reflection, and (4) creating an inclusive and non-discriminatory play and learning environment.